Over Expression of p5cs Gene to Increase Cold Stress Tolerance in Iranian Species of Petunia - Jamshidnia, Maryam; Ghobadi, Cyrus; Tabatabaei, Badraldin Ebrahim Sayed; Yamchi, Ahad (Plant Tissue Culture and Biotechnology, 2018)
In order to examine the relationship between proline and cold stress in Iranian (local) genotype of petunia, p5cs gene was transferred to petunia through Agrobacterium-mediated transformation. The leaf discs from four weeks and shoot apices from 7-day-old petunia in vitro plants were co-cultivated with Agrobacterium strain LBA4404 harboring a plasmid pBI121 as the vector system for transformation of petunia. pBI121 plasmid containing β-glucuronidase (gus) gene as a reporter gene and Δ1-pyrroline-5-carboxylate synthetase (p5cs) gene and neomycin phosphotransferase (nptII) gene were used as a selectable marker. The co-cultivated leaf discs and shoot apices were transferred to the selective medium and thereafter to proliferation medium respectively. To confirm transformation, regenerated plants were subjected to the polymerase chain reaction (PCR), GUS histochemical and proline assays. The results confirmed the presence of the gus and p5cs gene in the genome of all transformants and the transformed plants were more tolerant (674.87 μg/g fresh leaves) than the wild types under stress conditions. Plant Tissue Cult. & Biotech. 28(1): 35-44, 2018 (June)